MENJELAJAHI PENERAPAN KONSEP MASLAHAH MURSALA DALAM HUKUM KELUARGA ISLAM: STUDI KASUS ISTRI MENCARI NAFKAH DAN SUAMI BERTANGGUNG JAWAB ATAS PEKERJAAN RUMAH TANGGA - Firdaus, Firdaus Firdaus; Desminar, Desminar Desminar; Halim, Syaflin; Mursal, Mursal Mursal (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2023)
This research aims to apply the concept of maslahah murrasa in Islamic family law, using a case study of a wife who is looking for a husband who can carry out household duties. The concept of maslahah murlah is one of the principles of Islamic law which prioritizes the public benefit and accommodates the needs of a developing society. The research method used is qualitative research with a case study approach. Data was collected through in-depth interviews with a number of respondents who have experience in finding a life partner who can carry out household duties. Data analysis was conducted using an inductive approach, involving data collection, coding, and understanding the findings that emerged. The research results show that the concept of maslahah murlah can be applied in the context of finding a life partner who can carry out household duties. In this case, maslahah murlah can be interpreted as an effort to achieve balance in the roles and responsibilities between husband and wife in the household. It is hoped that the results of this research can contribute to the understanding and implementation of the concept of maslahah murlah in Islamic family law, especially in the context of finding a life partner who can carry out household duties. This research can also be a source of information and guidance for individuals who are looking for a life partner who suits their household needs